105k views
4 votes
Given that f(x) = 3x + 2 and h(x) = x3, find (h o f)(2).

User ShurupuS
by
6.0k points

1 Answer

1 vote

Answer/Step-by-step explanation:

This is what we know...

f(x) = 3x + 2 and h(x) = 3x and that h(2) or x=2

Given that info we can input our values into the variables.

f(2) = 3(2) + 2

Now according to the Order of Operations, we should multiply next.

f(2) = 6 + 2

Now according to the Order of Operations, we should add.

f(2) = 8

I don't know if your question wants it as a ordered pair or not so ignore this if there is any of those. The answer in an ordered pair would be (2,8)

Now we have to do the other equation.

Input our values into the variables

h(2) = 3(2)

Now according to the Order of Operations, we should multiply next.

h(2) = 6

I don't know if your question wants it as a ordered pair or not so ignore this if there is any of those. The answer in an ordered pair would be (2,6)

Hope this Helps! :)

If you have any extra questions, comment them and I will try my best to answer!

-SGO

User Mariotomo
by
5.2k points